2020
DOI: 10.3390/molecules25184173
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Biocatalysis on D/H Ratio: Possible Fundamental Differences for High-Level Biological Taxons

Abstract: The kinetics of biological reactions depends on the deuterium/protium (D/H) ratio in water. In this work, we describe the kinetic model of biocatalytic reactions in living organisms depending on the D/H ratio. We show that a change in the lifetime or other characteristics of the vital activity of some organisms in response to a decrease or increase in the content of deuterium in the environment can be a sign of a difference in taxons. For animals—this is a curve with saturation according to the Gauss’s princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The study of the biological activity of aqueous dilutions of EHS in the presence of fluoroquinolone supplement was carried out using the cell culture Spirostomum ambigua [75][76]. The mechanism of ligand-receptor interaction includes the stage of interaction of the xenobiotic with the cell, the disintegration of the intermediate complex, accompanied by a change in the concentration of the cellular biosensor due to conformational changes in the receptor, degradation, synthesis of new receptors and the formation of the intermediate state C• Ln (Figure 12).…”
Section: Spirotox Methodsmentioning
confidence: 99%
“…The study of the biological activity of aqueous dilutions of EHS in the presence of fluoroquinolone supplement was carried out using the cell culture Spirostomum ambigua [75][76]. The mechanism of ligand-receptor interaction includes the stage of interaction of the xenobiotic with the cell, the disintegration of the intermediate complex, accompanied by a change in the concentration of the cellular biosensor due to conformational changes in the receptor, degradation, synthesis of new receptors and the formation of the intermediate state C• Ln (Figure 12).…”
Section: Spirotox Methodsmentioning
confidence: 99%
“…Taken together these data suggest a higher efficacy of proliferation and a pool of investigation and support the idea to investigate the effects of DDW on cell proliferative activity and antitumor effects, as well as changes in the endogenous antioxidant system and non-specific resistance of the organism [ 20 , 21 ]. The results have shown that studies in this field are promising, as very interesting and encouraging data were obtained on the effects produced by shifts in protium and deuterium body content on cell proliferation and apoptosis [ 22 , 23 , 24 , 25 ]. However, the expansion of these studies has led to the emergence of diametrically opposed data, the analysis of which shows that the evaluation of certain processes at the cellular level requires fundamental information about the metabolism of hydrogen isotopes in the organism.…”
Section: Identified Molecular and Physiological Effects Of Deuteriummentioning
confidence: 99%
“…For the basket plant (Callisia fragrans L.), it was found that the redistribution and assimilation of mineral components goes fastertwo or more times-in deuterium-depleted water compared to water with natural isotopic composition. This allowed using Callisia as a model object of saturation with microelements, in particular, zinc [20,37].…”
Section: Plant Objectsmentioning
confidence: 99%
“…In the study of moss of this species, a significant difference in the peptide composition in waters with different D/H ratios was found (fig. 7) [37]. It should be noted that the sprouting of moss was carried out by hydroponics, i.e.…”
Section: Plant Objectsmentioning
confidence: 99%